THE EFFECTS SOCIAL CAPITAL ATTRIBUTES ON THE EMPLOYABILITY READINESS AMONG ENGINEERING GRADUATES IN THE HIGH EDUCATION INSTITUTE’S IN OMAN - Hinai, Masoud Rashid Al; Bhuiyan, Abul Bashar; Husin, Nor Azilah (International Journal of Business and Management Future, 2021)
The aim of this study is to investigate the effects of Social Capital attributes on the employability readiness of the engineering graduates of the High Education Institutes in Oman. The study adopted a self-directed structured questionnaire was distributed to a sample of engineering students and graduates from a number of colleges and universities. The study used structural equation modelling (SEM) for analysed the collected data. The findings of the statistical analysis of the study showed the significant contribution of social activities in the attainment of teamwork, communication, proficiency of the English language, and problem-solving skills. As a result, the involvement of the graduates in social activities strongly influences the awareness of career information which in return affects positively graduates’ Readiness for Employability. Specifically, study findings showed Social capital attributes factor could have a high influence on the Readiness for Employability of the graduates in Oman when it is utilised effectively. Finally, the study’s implementations and recommendations could be transferred to the Gulf and Arab or other countries’ contexts having similar settings of HE systems and similar issues of skills gap and employability concern of their graduates.